WHY REDUCE AND FIX AN ISOLATED AND DISPLACED ACROMIAL FRACTURE? REPORT OF A CASE (International Journal of Medicine & Health Research (IJMHR) (ISSN 2395-3586), 2024)
The fracture of the acromion is rare, only 8% of all scapular fractures. The purpose of the clinical case is to highlight the rarity of this condition, and the indication of surgical treatment to prevent subsequent functional damages as well as chronic pain conditions. We report the case of a 54-year-old patient who suffered a fall from a high height on the right shoulder following which he presented pain and total functional impotence of the upper limb without neurovascular disorders. The diagnosis of the acromion fracture was suspected by physical examination and confirmed by imaging. The treatment consisted of an open reduction with racking fixation. Then, reeducation was started early. The evolution was marked by the disappearance of the pain and the resumption of a good mobility of the shoulder after a retreat of 6 months. The fracture of the acromion is a rare condition that occurs following direct violent trauma. The scanner plays an important role in the management. Surgical treatment is intended to avoid complications and to obtain a functional shoulder especially in displaced forms.